A filterless scheme of generating frequency 16-tupling millimeter-wave based on only two MZMs. (August 2019) - Wang, Dongfei; Tang, Xianfeng; Xi, Lixia; Zhang, Xiaoguang; Fan, Yichen
Highlights: Simple system structure for generating 16-tupled frequency mm-wave signal. Cost effective only by two MZMs than previously reported. There is no requirement of filter to suppress unwanted harmonics. A high-quality 160 GHz mm-wave is obtained from a 10 GHz RF drive signal. Abstract: In this work, we propose a new scheme to generate high-quality frequency 16-tupling millimeter-wave only by two Mach-Zehnder modulators (MZM) and without filter. The two MZMs, biased at maximum transmission point, are used for odd order sidebands suppression. By controlling the modulation index of the MZM, ±4 th -order sidebands amplitude return zero. By adjusting phase shifter and the attenuator to cancel 0 th -order sideband; By adjusting the phase difference between RF driving signals of two subsystems to cancel ±(4n-2) th -order optical sidebands. The feasibility of the proposed were demonstrated and discussed. Simulation results show that using 10 GHz RF signal to drive the MZMs, 160 GHz mm-wave signal with 31.35 dB optical sideband suppression ratio (OSSR) and 24.11 dB radio frequency sideband suppression ratio (RFSSR) was obtained. The results are coincide with the theoretical analysis. Furthermore, the non-ideal cases are also analyzed. Even if the modulation index, the MZM bias voltage or extinction ratios deviate from the ideal values to a certain degree, the mm-wave signals' performance are still acceptable.